2005
DOI: 10.1121/1.1855035
|View full text |Cite
|
Sign up to set email alerts
|

Statistics and vertical directionality of low-frequency ambient noise at the North Pacific Acoustics Laboratory site

Abstract: We examine statistical and directional properties of the ambient noise in the 10-100 Hz frequency band from the NPAL array. Marginal probability densities are estimated as well as mean square levels, skewness and kurtoses in third octave bands. The kurotoses are markedly different from Gaussian except when only distant shipping is present. Extremal levels reached approximately 150 dB re 1 micro Pa, suggesting levels 60dB greater than the mean ambient were common in the NPAL data sets. Generally, these were pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…[5] The Billboard Array site was close to shipping lanes, the known migration routes of marine mammals, and epicenters of micro-earthquakes associated with convergence of the North American and Pacific Ocean plates [Worcester and Spindel, 2005;Baggeroer et al, 2005]. In individual data segments, localized, transient noise sources either of biological origin or due to nearby shipping and microearthquakes usually dominate over contributions of distributed noise sources, such as distant shipping and breaking water waves on the ocean surface.…”
Section: Npal Billboard Array Experimentsmentioning
confidence: 99%
“…[5] The Billboard Array site was close to shipping lanes, the known migration routes of marine mammals, and epicenters of micro-earthquakes associated with convergence of the North American and Pacific Ocean plates [Worcester and Spindel, 2005;Baggeroer et al, 2005]. In individual data segments, localized, transient noise sources either of biological origin or due to nearby shipping and microearthquakes usually dominate over contributions of distributed noise sources, such as distant shipping and breaking water waves on the ocean surface.…”
Section: Npal Billboard Array Experimentsmentioning
confidence: 99%
“…In individual data segments, localized, transient noise sources either of biological origin or due to nearby shipping and micro-earthquakes usually dominate over contributions of distributed noise sources, such as distant shipping and breaking water waves on the ocean surface. Statistics of the noise field at the experimental site exhibit strong deviations from Gaussianity when the field is dominated by localized noise sources (Baggeroer et al, 2005). Therefore, the contributions of localized noise sources can be suppressed, and diffusivity of the noise field can be effectively enhanced by excluding data segments with non-Gaussian noise from time averages.…”
Section: Resultsmentioning
confidence: 98%
“…To investigate the feasibility of passive acoustic tomography of the ocean, we re-examined noise data obtained by the NPAL Group during the 1998-1999 Billboard Array Experiment (Worcester and Spindel, 2005;Baggeroer et al, 2005). The data have been made available for this study by Dr. P. F. Worcester.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T-phases (T being an abbreviation for tertiary, following P, primary, and S, secondary, phases) are waterborne seismic waves created by P and S wave components propagating through and refracting, diffracting, and scattering from the ocean bottom into the water column. First described by Tolstoy et al (1949), T-phases are frequently recorded by passive acoustic sensor systems in the deep ocean (e.g., Baggeroer et al, 2005). A definitive review of T-phase research is found in Okal (2008).…”
Section: Introductionmentioning
confidence: 99%